Analyzing the factors and effects of water supply disruption in Penang Island, Malaysia - Muhammad Fakruhayat Ab Rashid,; Azimah Abd Rahman,; Siti Masayu Rosliah Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Water resources are nature's most precious gift in life on this earth. Humans need to have ethics in environmental development to caring the environment. The rapid development to meet human needs and requirements has caused the source of clean water supply to be more limited and threatened. This study aims to analyze the factors and effects of water supply disruption to the community in Penang Island. This study employs a quantitative approach, with a survey consisting of 100 questionnaires distributed to respondents. The study also uses an informal interview method that records some of the respondents’ thoughts and opinions about the research issues. Respondents were selected randomly to be involved in the data collection process. The results of the data were analyzed to obtain the value of frequency, percentage, mean, std. deviation, and descriptive analysis. According to the study's findings, the most influential factor of disruption of water supply consumption is a lack of capacity of the water treatment plants, which recorded a total mean=4.36, and the least influential factor is weaknesses in water management, which recorded a total mean=3.48. The most dominant effect of water supply disruption is the disease that affects health, with a mean score of 4.30, the least influential effect is a reduction in the life of flora and fauna, with a mean score of 3.61. This study has the potential to provide information to authorities and stakeholders in formulating strategies and interventions for the well-being of the community. The recommendation for future studies is to further expand the scope of the study which is to add more survey stations and the number of samples to describe the actual population.